Pengaruh Konten Marketing dan Influence Terhadap Minat Beli pada Ayam Krispi di Kota Bandung - Jasmine Hasna Rinjani Alifah; Halimah Zahrah; Indra Sasangka (Indo Publishing, 2026)
The development of social media, particularly Instagram, has changed the way consumers search for information and make purchasing decisions, including for local culinary products. This study aims to analyze the influence of Instagram Content Marketing and Influencers on consumers’ Purchase Intention toward Ayam Krispi Katsurupan Bandung. This research employs a quantitative approach using a survey method. The research sample consists of thirty-one respondents selected through purposive sampling, with criteria including individuals aged fifteen to fifty years, domiciled in Bandung and its surrounding areas, and having previously purchased Ayam Krispi Katsurupan products. Data were collected using a Likert scale questionnaire ranging from one to five, consisting of sixteen statement items that have been tested for validity and reliability. Data analysis was conducted using multiple linear regression with SPSS version twenty-six, including classical assumption tests, t-test, F-test, and coefficient of determination (R²).